2022
DOI: 10.21203/rs.3.rs-2159328/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Altered spontaneous brain activities in maintenance hemodialysis patients with cognitive dysfunction and the construction of cognitive function prediction models

Abstract: Trial registration:The study was approved by the Ethics Committee of the Second People's Hospital of Changzhou City (KY032-01). OBJECTIVE: To measure changes in spontaneous brain activity in maintenance hemodialysis patients (MHD) with cognitive impairment (CI) base on resting-state functional magnetic resonance imaging (rs-fMRI) and predict cognitive function in maintenance hemodialysis patients by combining spontaneous brain activity and clinical indicators. METHODS: We selected 50 patients undergoing mainte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…16 The significant correlation of plasma MIF levels with total WMH Fazekas scores indicated that MIF could be associated with WMH development and positively mirror the severity of WMH, which was further supported by the finding of differences in MIF plasma levels between the Fazekas score subgroups. Furthermore, previous studies have reported that decreased activity in the PoCG.L 24 and increased activity in the DCG.R 25 and STG.R 26 are closely related to cognitive impairment, which is in line with our results. The present study found that plasma MIF levels were positively correlated with mALFF values of the STG.R in the CSVD-CI group.…”
Section: ■ Discussionsupporting
confidence: 93%
“…16 The significant correlation of plasma MIF levels with total WMH Fazekas scores indicated that MIF could be associated with WMH development and positively mirror the severity of WMH, which was further supported by the finding of differences in MIF plasma levels between the Fazekas score subgroups. Furthermore, previous studies have reported that decreased activity in the PoCG.L 24 and increased activity in the DCG.R 25 and STG.R 26 are closely related to cognitive impairment, which is in line with our results. The present study found that plasma MIF levels were positively correlated with mALFF values of the STG.R in the CSVD-CI group.…”
Section: ■ Discussionsupporting
confidence: 93%